2018
DOI: 10.1093/jamiaopen/ooy028
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the use of the electronic health record for patient identification, communication, and clinical support in palliative care

Abstract: Objectives Globally, healthcare systems are using the electronic health record (EHR) and elements of clinical decision support (CDS) to facilitate palliative care (PC). Examination of published results is needed to determine if the EHR is successfully supporting the multidisciplinary nature and complexity of PC by identifying applications, methodology, outcomes, and barriers of active incorporation of the EHR in PC clinical workflow. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 43 publications
(122 reference statements)
0
46
0
2
Order By: Relevance
“…Overall, there is a dearth of literature on CDS development and implementation in the context of palliative care, as well as integration in an ED setting [34]. To date, what is known is that CDS tools can play an integral role in assisting healthcare providers in providing patients optimal care by providing patient-specific recommendations at the point of need [11,35].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there is a dearth of literature on CDS development and implementation in the context of palliative care, as well as integration in an ED setting [34]. To date, what is known is that CDS tools can play an integral role in assisting healthcare providers in providing patients optimal care by providing patient-specific recommendations at the point of need [11,35].…”
Section: Discussionmentioning
confidence: 99%
“…Three reviews focused on cancer, [21][22][23] others did not limit their inclusion criteria a specific disease. The reviews were carried out by research teams based in the following countries: USA (9), 17,[24][25][26][27][28][29][30][31] UK (6), 16,23,[32][33][34][35] Australia (2), 14,36 Canada (1) 22 Chile (1), 15 Denmark (1) 37 and Brazil (1) 38 .…”
Section: Characteristics Of the Included Reviewsmentioning
confidence: 99%
“…Thirteen reviews referenced the role of DHIs in monitoring, assessing, and managing physical and psychological symptoms. [14][15][16][17][22][23][24][25]27,30,31,34,37 EHRs were used to record symptoms 27,34 while telephone and videoconferencing were frequently used to monitor, assess and treat symptoms. 15,22,23,25,30,37,39 Some reviews described positive impacts of DHIs on symptom management, while most reviews identified inconsistent evidence or noted that evaluation of impact in many studies was lacking.…”
Section: Symptom Managementmentioning
confidence: 99%
See 2 more Smart Citations